CHM141: Chemistry / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2020)
This introductory course in basic chemistry includes fundamental concepts like atomic structures, general features in a periodic table and the various types of chemical bonds. This course also gives a brief introduction on the types of crystal structures and the general properties of the first series of transition elements. Besides the basic concepts, problem solving skills will be taught in topics like chemical stoichiometry, thermochemistry, electrochemistry, acids and bases.